Diagnóstico y determinación de la concentración de mercurio, arsénico y antimonio en sedimento marino del canal de Jambelí y su incidencia en la Biota - Valarezo Alonzo, Rosita América (2008)
It was made the diagnosis and determination of the concentration of antimony arsenic and mercury in marine sediment of the cannel of Jambelí and its incidence in the biota, by which samples took shelter of four points of this channel, with a 5 depth of centimeter and another one of 30 centimeter for each point.